2017
DOI: 10.7717/peerj.3156
|View full text |Cite
|
Sign up to set email alerts
|

Influences of ABO blood group, age and gender on plasma coagulation factor VIII, fibrinogen, von Willebrand factor and ADAMTS13 levels in a Chinese population

Abstract: BackgroundABO blood group is a hereditary factor of plasma levels of coagulation factor VIII (FVIII) and von Willebrand factor (VWF). Age and gender have been shown to influence FVIII, VWF, fibrinogen (Fbg), and ADAMTS13 (A disintegrin and metalloprotease with thrombospondin type 1 motif, 13). We investigated the effects of ABO type, age, and gender on plasma levels of FVIII, Fbg, VWF, and ADAMTS13 in a Chinese population.MethodsA total of 290 healthy volunteers were eligible for this study. ABO blood group wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
0
19
0
3
Order By: Relevance
“…Furthermore, numerous studies generally reported that plasma vWF and FVIII levels were significantly lower in O-group than non-O-group individuals [ 19 21 ].Similarly, our study showed vWF: Ag and FVIII:C were significantly lower in O-group than in non-O-group in HA blood donors ( p< 0.05). In another large-scale study on LA blood donors, we also found the levels of vWF and FVIII were significantly lower in O-group than non-O-group [ 22 ]. This could also provide reference for FFP preparation.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, numerous studies generally reported that plasma vWF and FVIII levels were significantly lower in O-group than non-O-group individuals [ 19 21 ].Similarly, our study showed vWF: Ag and FVIII:C were significantly lower in O-group than in non-O-group in HA blood donors ( p< 0.05). In another large-scale study on LA blood donors, we also found the levels of vWF and FVIII were significantly lower in O-group than non-O-group [ 22 ]. This could also provide reference for FFP preparation.…”
Section: Discussionmentioning
confidence: 98%
“…The reason why the effects of the ADAMTS13 SNP on the survival outcomes were not found in the female recipients is unknown. A recent study [25] has reported that blood levels of ADAMTS13 antigens were higher in females than in males, which may suggest that female recipients have a greater amount of ADAMTS13 antigen in the blood and are less likely to be affected by the ADAMTS13 SNP than male recipients, although this is highly speculative. Further studies will be needed to clarify whether the ADAMTS13 antigen can effectively protect transplant recipients against relapse.…”
Section: Discussionmentioning
confidence: 99%
“…And also 33 ABO-, age- and gender-matched offsprings of non-longevity families were recruited as controls (Normal group). The inclusion criteria of the participators were recruited as previously described and apheresis plasma of the participators was used in this study [27]. Briefly, all participators were over 18 years of age, healthy and unrelated.…”
Section: Methodsmentioning
confidence: 99%